2010
DOI: 10.1074/jbc.m109.087783
|View full text |Cite
|
Sign up to set email alerts
|

Requiem Protein Links RelB/p52 and the Brm-type SWI/SNF Complex in a Noncanonical NF-κB Pathway

Abstract: The SWI/SNF chromatin remodeling complex plays pivotal roles in mammalian transcriptional regulation. In this study, we identify the human requiem protein (REQ/DPF2) as an adaptor molecule that links the NF-B and SWI/SNF chromatin remodeling factor. Through in vitro binding experiments, REQ was found to bind to several SWI/SNF complex subunits and also to the p52 NF-B subunit through its nuclear localization signal containing the N-terminal region. REQ, together with Brm, a catalytic subunit of the SWI/SNF com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 41 publications
5
55
0
Order By: Relevance
“…Another possibility is the involvement of chromatin remodeling factors in the specific control of non-canonical NF-κB. In this regard, a recent study suggests that RelB/p52 is linked to the SWI/SNF chromatin remodeling complex via an adaptor protein, requiem [91]. In response to lymphotoxin stimulation, requiem forms a large complex with the SWI/SNF catalytic subunit, Brm, and RelB/p52, which is recruited to the promoter of the BLC gene.…”
Section: Nuclear Regulators Of P52/relbmentioning
confidence: 99%
“…Another possibility is the involvement of chromatin remodeling factors in the specific control of non-canonical NF-κB. In this regard, a recent study suggests that RelB/p52 is linked to the SWI/SNF chromatin remodeling complex via an adaptor protein, requiem [91]. In response to lymphotoxin stimulation, requiem forms a large complex with the SWI/SNF catalytic subunit, Brm, and RelB/p52, which is recruited to the promoter of the BLC gene.…”
Section: Nuclear Regulators Of P52/relbmentioning
confidence: 99%
“…Compared with the Luc activity of cells transfected with CV-1, the introduction of RelA/p50, RelB/p52, and c-Rel/p50 increased these reporter expression levels by 42-, 6-, and 3-fold, respectively (Fig. 1C, lanes 13,19, and 7 compared with lane 1). These results indicated that NF-B-MinP-Luc-A3 has very low basal NF-B activity and that none of the candidates have any effects alone under these conditions, even if expressed at high levels.…”
Section: High Expression Of Each Member Of the D4 Family And Phf10mentioning
confidence: 99%
“…For TNF-␣ stimulation, the cells were treated with 10 ng/ml TNF-␣ (R&D Systems, Minneapolis, MN). Vesicular stomatitis virus G protein (VSV-G)-pseudotyped retro-or lentiviral vectors were prepared as described previously (17,19). For transduction, cells were incubated with the virus vector stocks in the presence of 8 g/ml Sequabrene TM (Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations